Femtoelectron-Based Terahertz Imaging of Hydration State in a Proton Exchange Membrane Fuel Cell - P. Buaphad (2018)
© 2015, Springer Science+Business Media New York. Imbalanced water management in a proton exchange membrane (PEM) fuel cell significantly reduces the cell performance and durability. Visualization of water distribution and transport can provide greater comprehension toward optimization of the PEM fuel cell. In this work, we are interested in water flooding issues that occurred in flow channels on cathode side of the PEM fuel cell. The sample cell was fabricated with addition of a transparent acrylic window allowing light access and observed the process of flooding formation (in situ) via a CCD camera. We then explore potential use of terahertz (THz) imaging, consisting of femtoelectron-based THz source and off-angle reflective-mode imaging, to identify water presence in the sample cell. We present simulations of two hydration states (water and nonwater area), which are in agreement with the THz image results. A line-scan plot is utilized for quantitative analysis and for defining spatial resolution of the image. Implementing metal mesh filtering can improve spatial resolution of our THz imaging system.